Limitations in Pigeon Keeping: A Review - M. Ashraful Kabir (Journal of Multidisciplinary Applied Natural Science, 2021)
Pigeons are showing remarkable progress with more profit. This sector has many potential markets in the country. After visiting some pigeon houses, many limitations have been come out. Many rearers collect pigeons based on only physical appearance, and in the long run, they cannot get pure offspring. King pigeon is considered a table breed in the world but in Bangladesh rearers keep them as a common fancy item. Pigeons do not get their nutritious food from the owners. Result suggests that many rare pigeons are caught by predators and due to unwanted dirt in those lofts birds are affected by many diseases. Some remarkable farms are showing quality environment in their lofts and getting desirable profit.